The Positive Spiral Between Problem-Solving Management and Trust: A Study in Organizations for Individuals With Intellectual Disability - Estreder, Yolanda; Martínez-Tur, Vicente; Tomás, Inés; Maniezki, Alice; Ramos, José; Pătraş, Luminiţa (Frontiers in Psychology, 2021)
To achieve their goals, organizations for individuals with intellectual disability have to stimulate high-quality relationships between professionals and family members. Therefore, trust of professionals in family members has become a challenge. One relevant factor in explaining professional’s trust in families is the degree to which family members use the “problem-solving” conflict management strategy (high concern for oneself but also for the other party) in their disputes-disagreements with professionals. It is reasonable to argue that when family members use problem-solving conflict management, professional’s trust increases. Professional’s trust in turn stimulates the use of problem-solving strategies by family members. However, it is also plausible that professionals are the initiators of this positive spiral (professional’s trust – problem-solving conflict management by family members – professional’s trust). To examine this relationship between problem-solving and trust over time, we conducted a longitudinal survey study where 329 professionals reported on these two constructs three times (with a distance between the measurements of four weeks). Using structural equation modelling (SEM) methods with maximum likelihood (ML) estimation, we compared four nested models: a) stability; b) causality (where the problem-solving strategy by familiar members is the initiator of the spiral); c) reversed causation (where professional’s trust is the initiator of the spiral); and d) reciprocal (where problem-solving conflict management and trust reinforce each other). The results of the χ2 difference tests, regarding the comparison between models, proved that the reciprocal model was significantly superior than the alternative proposals. Our findings supported a complex view of the relationships between problem-solving conflict management and trust based on dynamic reciprocal relationships over time.